Mãe-esposa e professora: educadoras no final do século XIX - Pinheiro, Rossana Kess Brito de Souza (2009)
This text is organized through discussions undertaken in the area of the History of Education in Rio Grande do Norte, circumscribed to the History of Women from the first decades of the Brazilian Republic, and to the analysis of what was expected of this education. We examined representations of women in Natal, between 1889 and 1914, with the goal of configuring relations between the sexes with the emphasis on moral, intellectual and pedagogical aspects required of these women. As documental sources we utilized the educational, civil and criminal Legislation, on a National scope, as well as on a State and Municipal scope. We circumscribed our search to the newspaper A República, in which we found literature that circulated in Natal in the form of pamphlets, short stories and poetry, as well as other texts by authors that were part of the corpus of analysis of this study, located in public and private archives in Rio Grande do Norte, such as the Historical and Geographic Institute of Rio Grande do Norte (IHGRN) and the State Public Archive of Rio Grande do Norte (APE-RN). The use of the indexing method and the propositions of Cultural History were the appropriate theoretical-methodological framework to complete studies of this nature. This operational perspective permitted us to elaborate nuances about this time of transition from the 19th to the 20th Century, and to spotlight the fire of the women from this period. The basis of the argument that related women to maternity and domesticity, and within the ideals of abnegation and religious leadership, aligned to a demand coming from the increase in the quantity of schools for women, allocated women as the most appropriate for superior in educational performance in the country, based on its foundations: primary education. Beyond the universe of formal education, the other side of women appeared in republican politics. The mother-spouse and the institutionalization of domestic education associated the female gender with the role of educator at home as well. Be it in the public sphere, as a teacher, or in private, as mother-spouse, female care is perceived in this configuration, as an educational base that the Republic, and in transition, bequeathed to the Brazilian 20th Century